The Factors that Have Contributed to the Rampant Physical Punishment of Children Aged 5-12 : a case study of Buwenge town council - Mirembe, Sylivia (Kampala : Uganda Christian University, 2010)
Descriptive Cataloging Uganda Christian University Mukono. BCDM
includes bibliographical references and appendices.
Keywords: Child purnishment